Działania Unii Europejskiej na rzecz zwalczania antysemityzmu - Kosińska, Anna Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article analyses the activity undertaken at the European Union level in terms of combating anti-Semitism, which is a reminiscence of the totalitarian system that operated in Europe and that led to the outbreak of WWII and the Holocaust. The aim of the article is to investigate cohesion of political actions taken by EU institutions on the basis of existing legal basis and to assess their effectiveness in building a civil society free of prejudice. The article uses the method of investigation of the law in force and the method of text analysis to study EU’s political documents. They study analyses the achievements of the thought of the Founding Fathers of the Community, norms of primary and secondary legislation that guarantee protection against discrimination and hate crime, documents and the so-called soft law (atypical acts) adopted by EU institutions and actions taken by the Union’s bodies to eliminate anti-Semitism in the Member States.
Keywords: zakaz dyskryminacji; Unia Europejska; antysemityzm; prawa podstawowe